Ideological supervision of the printed materials in the USSR in the first half of the 20th of XX century - Valentyna Molotkina (Cхід, 2013)
Analyses the activities of the Soviet authorities to establish ideological control over the dissemination of printed materials in Ukraine in the lane floor 20th of XX century.